Sosialisasi Gerak Mobility Pada Siswa SMA Kabupaten Gowa - Muslim Bin Ilyas; Andi Sahrul Jahrir; Muhammad Ivan Miftahul Aziz; Muhammad Syachrul Syamsuddin; Harvina Mukrim (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the understanding and skills of high school students in Gowa Regency in carrying out mobility movements as part of efforts to maintain functional fitness and prevent the risk of injury. Good joint mobility is the main foundation in carrying out physical activities efficiently and safely, especially for adolescents who are in the growth phase. The method used is participatory practice-based socialization with an educational and interactive approach, involving PJOK teachers and students directly. The material provided includes basic concepts of mobility, dynamic mobility drills, and the application of exercises in daily routines. The results of the activity showed an increase in students' understanding of the importance of body mobility, increased movement skills, and the emergence of awareness of the importance of maintaining fitness through good mobility. Teachers also showed high enthusiasm in integrating mobility materials into learning. This activity was concluded to be effective in building a culture of movement and fitness awareness in the school environment, and is recommended to be replicated in other schools as part of physical education learning innovation.